Testing of Capital Asset Pricing Model (CAPM) During an Upward Trend in the Indian Stock Market - Kant, Ravi (Indian Journal of Finance, 2011)
This paper tests whether Capital Assets Pricing Model (CAPM) holds in the Indian stock market by applying the test for the intercept and the slop for the standard form of CAPM. The first objective of study is to ascertain the relationship between return of securities and market returns. The second objective of the study is to test the empirical validity of the standard CAPM in the Indian context. The third objective of study is to ascertain the relationship between returns of securities and market capitalisation (size). The empirical test of the CAPM is carried out by using the weekly data of 30 stock traded is the Mumbai Stock Exchange (BSE) during the period July, 2007 to Dec., 2007. Data has taken from The Economic Times news paper and PROWESS, while selecting the sample securities, sufficient care is taken to ensure that all sectors of industries were represented. This paper measures return and risk, correlation between two variables, alphas (intercept), coefficient of determination, T-statistics. The evidence from Tables shows a strong positive relation between individual stock excess return and markets index both in entire and sub period.